Big Data in Medicine, the Present and Hopefully the Future - Riba, Michela; Sala, Cinzia; Toniolo, Daniela; Tonon, Giovanni (Frontiers in Medicine, 2019)
The emergence of data coming from different venues, as several “omic” approaches, is providing already compelling evidence that the smart use of this information could provide invaluable information to prevent, diagnose and treat human diseases. However, the most daunting challenges remain ahead, as the explosive accumulation of data from additional perspectives, including social graphs, biosensors and imaging, promise to deliver crucial information that could be exploited for the improvement of the entire human race, both in developed and developing countries, optimizing health expenses and reaching also the less fortunate sections of the societies. And yet, formidable challenges remain, that pertain for the most part to the collection of the data, their organization, and most relevantly their integration. Here we provide few, pointed examples to the present relevance of these big data approaches in human health as well potential road maps towards the implementation of broader data collections and analyses.